Refrigerant-resistant HNBR sealing ring and preparation method thereof
By using HNBR and nano-modified aluminum magnesium silicate and other materials in the air conditioning seal ring of new energy vehicles, the problem of aging of the seal ring under long-term hot and cold cycles and refrigerant contact is solved, and the excellent aging resistance and seal stability of the seal ring are achieved, ensuring the long-term normal operation of the air conditioning system.
Patent Information
- Application Number
- CN202411957392.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-11
AI Technical Summary
The sealing ring of the air conditioner of new energy vehicles is prone to aging under long-term hot and cold cycles and refrigerant contact, reducing the stable performance of the long-term use of the air conditioner system.
HNBR is used as a matrix and combined with nanomodified aluminum magnesium silicate, white carbon black, plasticizer, crosslinking agent, active agent and anti-aging agent for compounding. Through uniform and stable crosslinking, a sealing ring with excellent aging resistance and sealing stability is produced.
Under long-term refrigerant conditions, the sealing ring maintains good aging resistance and sealing stability to prevent refrigerant leakage and ensure the long-term normal operation of the air conditioning system of new energy vehicles.
Smart Images

Figure BDA0005216234110000051 
Figure BDA0005216234110000061 
Figure BDA0005216234110000071
Abstract
Description
Technical Field
[0001] The present application relates to the field of rubber sealing rings, and more specifically, to a refrigerant-resistant HNBR sealing ring and a preparation method thereof. Background Art
[0002] The air conditioning system of new energy vehicles is an important part of ensuring a comfortable interior environment. With the rapid development of the new energy vehicle market, the performance requirements for air conditioning systems are getting higher and higher. The air conditioning seal ring of new energy vehicles is a ring-shaped part made of rubber material, which is used to seal the connection of air conditioning systems such as compressors, condensers, evaporators and battery packs. It prevents the leakage of refrigerants such as HFC-134a and maintains the sealing of the air conditioning system. It needs to have good flexibility, sealing stability and refrigerant resistance.
[0003] Currently, the materials used for air-conditioning sealing rings in new energy vehicles are generally soft PVC materials or silicone materials. Although they have good short-term sealing properties, during the continuous operation of new energy vehicles, the air-conditioning system undergoes long-term hot and cold cycles, and the air-conditioning sealing rings are exposed to refrigerant for a long time, which will still be prone to aging, reducing the long-term stability of the air-conditioning system. Summary of the invention
[0004] In order to solve the problem that the current new energy vehicle air-conditioning sealing ring is prone to aging due to long-term hot and cold cycles in the air-conditioning system and long-term contact with refrigerant, which reduces the long-term stability of the air-conditioning system, the present application provides a refrigerant-resistant HNBR sealing ring and a preparation method thereof.
[0005] In the first aspect, the present application provides a refrigerant-resistant HNBR sealing ring, which adopts the following technical solution: A refrigerant-resistant HNBR sealing ring is prepared from the following raw materials in parts by weight: HNBR 100-120 parts 45-55 parts of nano-modified magnesium aluminum silicate 40-50 parts of white carbon black Plasticizer 10-20 parts Crosslinking agent 6-10 parts Active agent 5-8 parts Vulcanizing agent 5-8 parts 1-3 parts of antioxidant. By adopting the above technical solution, the refrigerant-resistant HNBR sealing ring prepared in the present application is applied to the air conditioner of new energy vehicles, suitable for the environment of long-term cold and hot cycles, and has excellent aging resistance to refrigerants such as HFC-134a, so that the air conditioning system has stable sealing performance. The present application uses HNBR as the rubber matrix, and HNBR is hydrogenated nitrile rubber with excellent cold resistance and oil resistance. HNBR is compounded with nano-modified magnesium aluminum silicate, white carbon black, plasticizer, cross-linking agent, activator and antioxidant, which can play a good synergistic role. Nano-modified magnesium aluminum silicate, white carbon black and activator are evenly dispersed in the system to reinforce the performance of the system. Under the promotion of the activator and the vulcanization of the vulcanizer, the system is evenly and stably cross-linked to obtain a sealing ring with good cross-linking density and molecular structure density. Under long-term refrigerant conditions, it can maintain good aging resistance and sealing stability to prevent refrigerant leakage, and can maintain good flexibility for a long time to ensure the long-term normal operation of the air-conditioning system of new energy vehicles.
[0006] Preferably, the nano-modified magnesium aluminum silicate is prepared from the following raw materials in parts by weight: 80-100 parts of magnesium aluminum silicate 1-3 parts of polyethylene glycol 4000 1-3 parts of ammonium persulfate 2-4 parts of acrylic acid-acrylate-sulfonate terpolymer Silane coupling agent 4-8 parts Pentaerythritol triallyl ether 5-10 parts 8-12 parts of epoxy-terminated liquid nitrile rubber 150-180 parts of water.
[0007] Preferably, the nano-modified magnesium aluminum silicate is prepared by the following steps: A1. Add ammonium persulfate and acrylic acid-acrylate-sulfonate terpolymer into water, add magnesium aluminum silicate after dissolving, heat to 50-60° C., stir for 20-40 min, filter, wash with water, and dry to obtain pretreated magnesium aluminum silicate; A2. Knead and disperse the pretreated aluminum magnesium silicate, silane coupling agent, polyethylene glycol 4000, pentaerythritol triallyl ether and epoxy-terminated liquid nitrile rubber at a temperature of 70-90° C. for 1-2 hours to obtain nano-modified aluminum magnesium silicate.
[0008] By adopting the above technical scheme, ammonium persulfate and acrylic acid-acrylate-sulfonate terpolymer play a good synergistic role and can fully react with magnesium aluminum silicate in an aqueous solution to obtain pretreated magnesium aluminum silicate with high surface activity, thereby improving the modification efficiency of magnesium aluminum silicate. Then, polyethylene glycol 4000, silane coupling agent, pentaerythritol triallyl ether and epoxy-terminated liquid nitrile rubber are added to the pretreated magnesium aluminum silicate, and kneaded and dispersed under optimal temperature and time conditions to further modify the pretreated magnesium aluminum silicate. Polyethylene glycol 4000 has good wetting and dispersing properties. Under the action of silane coupling agent, the compatibility of pretreated magnesium aluminum silicate, pentaerythritol triallyl ether and epoxy-terminated liquid nitrile rubber can be further improved. The nano-modified magnesium aluminum silicate obtained in this way has good dispersibility and cross-linking stability. Under the action of vulcanizing agent, it can further cross-link with the system to further improve the structural density of the obtained sealing ring, thereby improving its flexibility and aging resistance. By optimizing the dosage ratio of each component, the magnesium aluminum silicate can be modified with less raw material dosage, thereby improving the modification efficiency of the magnesium aluminum silicate.
[0009] Preferably, the silane coupling agent is composed of A174 silane coupling agent and tetramethyltetravinylcyclotetrasiloxane in a weight ratio of 1:(0.5-1).
[0010] By adopting the above technical scheme, compounding with A174 silane coupling agent and tetramethyltetravinylcyclotetrasiloxane in a relatively optimal weight ratio, the coupling performance of pretreated magnesium aluminum silicate with pentaerythritol triallyl ether and terminal epoxy liquid nitrile rubber can be improved, and the dispersion stability of the prepared nano-modified magnesium aluminum silicate and the system can be further improved.
[0011] Preferably, the white carbon black is alkaline precipitated white carbon black with a particle size of 10-20 μm.
[0012] By adopting the above technical scheme, the alkaline precipitated silica has a larger particle size than the fumed silica. Although its comprehensive performance is not as good as that of the fumed silica, it is cheap and more suitable for industrial production. In the formulation system of the present application, alkaline precipitated silica with a particle size of 10-20 μm is selected for performance reinforcement, which can have a good interface bonding force with the system. The prepared HNBR sealing ring can maintain the same effect as the formulation using fumed silica in the prior art, and the prepared sealing ring has good mechanical strength and aging resistance.
[0013] Preferably, the plasticizer is composed of di(butoxyethoxyethyl) adipate and dibutyl itaconate in a weight ratio of 1:(2-3).
[0014] By adopting the above technical scheme, using di(butoxyethoxyethyl) adipate and dibutyl itaconate in a relatively optimal weight ratio as plasticizers, the softness and processability of the HNBR sealing ring can be effectively improved, while ensuring its strength and refrigerant resistance under low temperature conditions.
[0015] Preferably, the crosslinking agent is composed of triallyl isocyanurate and pentaerythritol diacrylate monostearate in a weight ratio of (1-2):1.
[0016] By adopting the above technical scheme, using triallyl isocyanurate and pentaerythritol diacrylate monostearate in a preferred weight ratio as cross-linking agents, it is possible to further cross-link with the HNBR system, thereby improving the molecular structure stability of the obtained sealing ring, and effectively improving the mechanical strength and refrigerant resistance of the sealing ring.
[0017] Preferably, the vulcanizing agent is 2,4-di-tert-butyl cumene peroxide.
[0018] By adopting the above technical scheme and using 2,4-di-tert-butyl peroxide isopropylbenzene as a vulcanizing agent, the vulcanization reaction of HNBR can be effectively promoted, the vulcanization time can be shortened, the production efficiency can be improved, and the mechanical strength and aging resistance of the prepared HNBR sealing ring can be improved.
[0019] Preferably, the antioxidant is a phenolic antioxidant and / or an amine antioxidant.
[0020] By adopting the above technical solution, the use of phenolic antioxidants and / or amine antioxidants improves the antioxidant properties of HNBR sealing rings, extends the service life of the sealing rings in long-term hot and cold cycle environments and refrigerant contact environments, and improves the long-term stability and reliability of new energy vehicle air-conditioning systems.
[0021] In a second aspect, the present application provides a method for preparing a refrigerant-resistant HNBR sealing ring, using the following technical solution: A method for preparing a refrigerant-resistant HNBR sealing ring comprises the following steps: S1, mixing: mixing HNBR, nano-modified aluminum magnesium silicate, white carbon, an active agent, a plasticizer, a cross-linking agent and an antioxidant to obtain a mixed material; S2, slicing: adding a vulcanizing agent to the mixed material, mixing, tableting, extruding, and slicing to obtain a prefabricated sheet; S3, compression molding: the prefabricated sheet is compression-vulcanized and punched to obtain a refrigerant-resistant HNBR sealing ring.
[0022] By adopting the above technical scheme, HNBR is firstly mixed with nano-modified aluminum magnesium silicate, white carbon black, active agent, plasticizer, cross-linking agent and antioxidant to improve the overall uniformity of the material and the compatibility between the components, thereby ensuring the mechanical properties and processing properties of the sealing ring. Secondly, a vulcanizing agent is added to the mixture for further mixing to obtain a preform with good vulcanization performance, and then the preform is vulcanized and cross-linked by compression vulcanization molding, and finally punched to remove the scraps, so that the HNBR sealing ring obtained has good surface flatness, aging resistance and sealing stability.
[0023] In summary, this application has the following beneficial effects: 1. The refrigerant-resistant HNBR sealing ring of the present application is made of HNBR, nano-modified aluminum magnesium silicate, white carbon black, plasticizer, cross-linking agent, activator, vulcanizing agent and antioxidant. Under the action of the vulcanizing agent, the system is uniformly and stably cross-linked to obtain a sealing ring with good cross-linking density and molecular structure density. It is used in new energy vehicle air conditioners, has excellent aging resistance to refrigerants such as HFC-134a, is suitable for long-term hot and cold cycle environments, has stable sealing performance and flexibility for the air-conditioning system, prevents refrigerant leakage, and ensures the long-term normal operation of the air-conditioning system of new energy vehicles.
[0024] 2. The composition of nano-modified magnesium aluminum silicate was further optimized. The magnesium aluminum silicate was modified with polyethylene glycol 4000, ammonium persulfate, acrylic acid-acrylate-sulfonate terpolymer, silane coupling agent, pentaerythritol triallyl ether, epoxy-terminated liquid nitrile rubber and water. The nano-modified magnesium aluminum silicate obtained in this way has good dispersibility and cross-linking stability. It can further undergo cross-linking reaction with the system under the action of a vulcanizing agent, thereby further improving the structural density of the obtained sealing ring, thereby improving its flexibility and aging resistance.
[0025] 3. Using di(butoxyethoxyethyl) adipate and dibutyl itaconate in a preferred weight ratio as plasticizers, and triallyl isocyanurate and pentaerythritol diacrylate monostearate in a preferred weight ratio as cross-linking agents can further improve the molecular structure stability and flexibility of the prepared sealing ring, and can effectively improve the mechanical strength and refrigerant resistance of the sealing ring. DETAILED DESCRIPTION
[0026] The present application is further described in detail below with reference to the embodiments.
[0027] The following are the sources and specifications of some raw materials of this application. The raw materials used in the preparation examples and embodiments of this application can be obtained from the market, including but not limited to the raw materials of the following models and manufacturers. Raw materials with equivalent performance can be used: 1. HNBR: LANXESS Chemical, model Therban3407; 2. White carbon black: alkaline precipitated white carbon black, TOKUSIL 923 from Taiwan, China; 3. Active agent: zinc oxide, Actmix ZnO-80GE; 4. Magnesium aluminum silicate: KMIK, CAS No. 12511-31-8, content 99%; 5. Acrylic acid-acrylate-sulfonate terpolymer: Pande, content 30%; 6. Epoxy-terminated liquid nitrile rubber: Green Union Chemical, model TL910; 7. Di(butoxyethoxyethyl) adipate: Model TP-95; 8. Dibutyl itaconate: CAS No. 2155-60-4, content 99%; 9. Triallyl isocyanurate: CAS No. 1025-15-6, crosslinking agent TAIC; 10. Pentaerythritol diacrylate monostearate: CAS No. 92092-01-8.
[0028] Preparation example of nano-modified magnesium aluminum silicate Preparation Example 1 Preparation Example 1 discloses a nano-modified magnesium aluminum silicate, which is prepared by the following steps: A1, adding 0.1kg of ammonium persulfate and 0.2kg of acrylic acid-acrylate-sulfonate terpolymer to 15kg of water, adding 8kg of magnesium aluminum silicate after dissolving, heating to 50°C, stirring for 40min, filtering, washing with water, and drying to obtain pretreated magnesium aluminum silicate; A2, kneading and dispersing the pretreated magnesium aluminum silicate obtained in step A1, 0.1kg of polyethylene glycol 4000, 0.8kg of silane coupling agent (composed of KH560 and A171 in a weight ratio of 1:1), 1kg of pentaerythritol triallyl ether and 0.8kg of epoxy-terminated liquid nitrile rubber at a temperature of 90°C, kneading for 1h to obtain nano-modified magnesium aluminum silicate.
[0029] Preparation Example 2-3 The difference between Preparation Example 2-3 and Preparation Example 1 is that the amount of raw materials used and the preparation conditions are different, see Table 1 below for details.
[0030] Table 1 Parameters of Preparation Examples 1-3 Preparation Example 4 The difference between Preparation Example 4 and Preparation Example 1 is that an equal amount of acrylic acid-acrylate-sulfonate terpolymer is replaced by sodium dodecylbenzenesulfonate, and the rest is the same as Preparation Example 1.
[0031] Preparation Example 5 The difference between Preparation Example 5 and Preparation Example 1 is that an equal amount of the epoxy-terminated liquid nitrile rubber is used to replace pentaerythritol triallyl ether, and the rest is the same as Preparation Example 1.
[0032] Preparation Example 6 The difference between Preparation Example 6 and Preparation Example 1 is that an equal amount of pentaerythritol triallyl ether is replaced by vinyl trimethoxy silane, and the rest is the same as Preparation Example 1.
[0033] Preparation Example 7 The difference between Preparation Example 7 and Preparation Example 1 is that the silane coupling agent in Preparation Example 7 is composed of A174 silane coupling agent and tetramethyltetravinylcyclotetrasiloxane in a weight ratio of 1:1, and the rest is the same as Preparation Example 1.
[0034] Preparation Example 8 The difference between Preparation Example 8 and Preparation Example 1 is that the silane coupling agent in Preparation Example 8 is composed of A174 silane coupling agent and tetramethyltetravinylcyclotetrasiloxane in a weight ratio of 1:0.5, and the rest is the same as Preparation Example 1. Example
[0035] Example 1 Example 1 discloses a refrigerant-resistant HNBR sealing ring, which is prepared by the following steps: S1, mixing: 10kg HNBR, 5.5kg commercially available nano-modified aluminum magnesium silicate, 4kg white carbon black, 0.5kg zinc oxide as an active agent, 1kg plasticizer (composed of dioctyl phthalate and dibutyl itaconate in a weight ratio of 1:2), 1kg triallyl isocyanurate as a cross-linking agent and 0.1kg antioxidant 2246 were mixed, the mixing temperature was controlled to be 125° C., and the mixing was performed for 2.5 hours to obtain a mixed material; S2, slicing: cooling the mixture to 90°C, adding 0.5 kg of 2,4-di-tert-butyl peroxide isopropylbenzene as a vulcanizing agent to the mixture for mixing, mixing for 15 minutes, tableting, extruding, and slicing to obtain preformed sheets; S3. Compression molding: Place the prefabricated sheet into the mold of a molding vulcanizer, close the mold for compression vulcanization molding, control the vulcanization temperature to 175°C, vulcanize for 5 minutes, take it out and use a stamping equipment to punch out the scraps to obtain a refrigerant-resistant HNBR sealing ring; nano-modified aluminum magnesium silicate comes from the commercially available, Ruiba New Materials, model N95.
[0036] Example 2-3 The difference between Example 2-3 and Example 1 is that the amount of raw materials used and the preparation conditions are different, see Table 2 below for details.
[0037] Table 2 Parameters of Examples 1-3 Embodiment 4-11 The difference between Example 4-11 and Example 1 is that the sources of the modified nano-magnesium aluminum silicate are different, see Table 3 below for details.
[0038] Table 3 Sources of modified nano-magnesium aluminum silicate of Examples 4-11 Example Source of modified nano-magnesium aluminum silicate Example 4 Preparation Example 1 Example 5 Preparation Example 2 Example 6 Preparation Example 3 Example 7 Preparation Example 4 Example 8 Preparation Example 5 Example 9 Preparation Example 6 Example 10 Preparation Example 7 Embodiment 11 Preparation Example 8 Example 12 The difference between Example 12 and Example 10 is that the plasticizer in Example 12 consists of di(butoxyethoxyethyl) adipate and dibutyl itaconate in a weight ratio of 1:2, and the rest is the same as Example 10.
[0039] Embodiment 13 The difference between Example 13 and Example 10 is that the plasticizer in Example 13 consists of di(butoxyethoxyethyl) adipate and dibutyl itaconate in a weight ratio of 1:3, and the rest is the same as Example 10.
[0040] Embodiment 14 The difference between Example 14 and Example 12 is that the cross-linking agent in Example 14 is composed of triallyl isocyanurate and pentaerythritol diacrylate monostearate in a weight ratio of 1:1, and the rest is the same as Example 12.
[0041] Embodiment 15 The difference between Example 15 and Example 12 is that the cross-linking agent in Example 15 is composed of triallyl isocyanurate and pentaerythritol diacrylate monostearate in a weight ratio of 2:1, and the rest is the same as Example 12.
[0042] Comparative Example Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that the modified nano-magnesium aluminum silicate is replaced by white carbon black in equal amount, and the rest is the same as Example 1.
[0043] Performance testing The following is a performance test of the refrigerant-resistant HNBR sealing rings prepared in Examples 1-15 and Comparative Example 1: The HNBR sealing rings with an inner diameter of 15 mm and a cross-sectional diameter of 1.8 mm were used as test samples for the test.
[0044] 1. Refrigerant resistance test: The sealing ring was soaked in pressurized liquefied HFC-134a refrigerant for 72 hours. The sealing ring after soaking test was assembled at the joint position of the compressor of the new energy vehicle air conditioner to make a test product. The air tightness test was carried out as follows: a helium mass spectrometer leak detector and a digital pressure gauge were used. At 25°C, the test product was placed in the helium mass spectrometer leak detector. The test pressure was adjusted to 2MPa, the helium concentration was kept greater than or equal to 80%, and the pressure was maintained for 60s. The gas leakage rate of the test product (unit: pa·m 3 / s), the smaller the gas leakage rate, the better the air tightness.
[0045] 2. Elongation at break test: The sealing ring is subjected to a double 85 test. After 1000 hours of testing, the elongation at break of the HNBR sealing ring is tested (unit: %) according to the test method in ASTM-D3574-08, and the test results are tested and recorded; The following are the performance test data of the HNBR sealing rings prepared in Examples 1-15 and Comparative Example 1, see Table 4 below for details.
[0046] Table 4 Data table of HNBR seal rings prepared in Examples 1-15 and Comparative Example 1 Combining Examples 1-3 and Comparative Example 1 and Table 4, it can be concluded that the use of nano-modified aluminum magnesium silicate and white carbon black for compounding can produce a good synergistic effect with the HNBR system, and improve the refrigerant resistance, aging resistance and flexibility of the prepared HNBR sealing ring. Compared with Example 1, Comparative Example 1 replaces the nano-modified aluminum magnesium silicate with white carbon black in equal amounts. After the refrigerant resistance test of the prepared HNBR sealing ring, the air tightness is significantly reduced, and the elongation at break is also significantly reduced. This may be because white carbon black is used alone as a reinforcing agent, and the dispersion uniformity in the HNBR system is low, which reduces the flexibility and stability of the prepared HNBR sealing ring.
[0047] Combining Examples 1-3 and Examples 4-11 and Table 4, it can be concluded that by further optimizing the preparation process of nano-modified magnesium aluminum silicate, the refrigerant resistance, aging resistance and flexibility of the prepared HNBR sealing ring are significantly improved. Compared with Example 1, in Examples 4-6, magnesium aluminum silicate is pretreated with ammonium persulfate and acrylic acid-acrylate-sulfonate terpolymer in a preferred weight ratio, and then modified with polyethylene glycol 4000, silane coupling agent, pentaerythritol triallyl ether and terminal epoxy liquid nitrile rubber, and the refrigerant resistance, aging resistance and flexibility of the obtained HNBR sealing ring are improved; while in Examples 7-9, the preparation raw materials can be changed, the synergistic effect of each component is reduced, and the refrigerant resistance, aging resistance and flexibility of the obtained HNBR sealing ring are reduced; and in Examples 10-11, compared with Example 4, the type of silane coupling agent is further optimized, and the performance of the obtained HNBR sealing ring is improved, which may be due to the selection of a preferred weight ratio of silane coupling agent, which improves the compatibility of the pretreated magnesium aluminum silicate with pentaerythritol triallyl ether and terminal epoxy liquid nitrile rubber.
[0048] Further combining Example 10 with Examples 12-13 and Examples 14-15 and Table 4, it can be concluded that further optimizing the composition of the plasticizer and crosslinking agent in the HNBR sealing ring of the present application can further improve the refrigerant resistance, aging resistance and flexibility of the HNBR sealing ring. The performance of the HNBR sealing ring finally obtained is optimal, and the refrigerant resistance airtightness reaches 1.8x10 -6 pa·m 3 / s, and the aging-resistant elongation at break reaches 284%.
[0049] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A refrigerant-resistant HNBR sealing ring, characterized in that: Made from the following raw materials in parts by weight: HNBR 100-120 parts 45-55 parts of nano-modified magnesium aluminum silicate 40-50 parts of white carbon black Plasticizer 10-20 parts Crosslinking agent 6-10 parts Active agent 5-8 parts Vulcanizing agent 5-8 parts 1-3 parts of antioxidant.
2. A refrigerant-resistant HNBR sealing ring according to claim 1, characterized in that: The nano-modified magnesium aluminum silicate is prepared from the following raw materials in parts by weight: 80-100 parts of magnesium aluminum silicate 1-3 parts of polyethylene glycol 4000 1-3 parts of ammonium persulfate 2-4 parts of acrylic acid-acrylate-sulfonate terpolymer Silane coupling agent 4-8 parts Pentaerythritol triallyl ether 5-10 parts 8-12 parts of epoxy-terminated liquid nitrile rubber 150-180 parts of water.
3. A refrigerant-resistant HNBR sealing ring according to claim 2, characterized in that: The nano-modified magnesium aluminum silicate is prepared by the following steps: A1. Add ammonium persulfate and acrylic acid-acrylate-sulfonate terpolymer into water, add magnesium aluminum silicate after dissolving, heat to 50-60° C., stir for 20-40 min, filter, wash with water, and dry to obtain pretreated magnesium aluminum silicate; A2. Knead and disperse the pretreated aluminum magnesium silicate, silane coupling agent, polyethylene glycol 4000, pentaerythritol triallyl ether and epoxy-terminated liquid nitrile rubber at a temperature of 70-90° C. for 1-2 hours to obtain nano-modified aluminum magnesium silicate.
4. A refrigerant-resistant HNBR sealing ring according to claim 2, characterized in that: The silane coupling agent is composed of A174 silane coupling agent and tetramethyltetravinylcyclotetrasiloxane in a weight ratio of 1:(0.5-1).
5. A refrigerant-resistant HNBR sealing ring according to claim 1, characterized in that: The white carbon black is alkaline precipitated white carbon black with a particle size of 10-20 μm.
6. A refrigerant-resistant HNBR sealing ring according to claim 1, characterized in that: The plasticizer is composed of di(butoxyethoxyethyl) adipate and dibutyl itaconate in a weight ratio of 1:(2-3).
7. A refrigerant-resistant HNBR sealing ring according to claim 1, characterized in that: The crosslinking agent is composed of triallyl isocyanurate and pentaerythritol diacrylate monostearate in a weight ratio of (1-2):
1.
8. The refrigerant-resistant HNBR sealing ring according to claim 1, characterized in that: The vulcanizing agent is 2,4-di-tert-butyl cumene peroxide, and the antioxidant is a phenol antioxidant and / or an amine antioxidant.
9. A method for preparing a refrigerant-resistant HNBR sealing ring according to any one of claims 1 to 8, characterized in that: The following steps are involved: The method for preparing a refrigerant-resistant HNBR sealing ring according to claim 9 is characterized in that: The following steps are involved: S1, mixing: mixing HNBR, nano-modified aluminum magnesium silicate, white carbon, an active agent, a plasticizer, a cross-linking agent and an antioxidant to obtain a mixed material; S2, slicing: adding a vulcanizing agent to the mixed material, mixing, tableting, extruding, and slicing to obtain a prefabricated sheet; S3, compression molding: the prefabricated sheet is compression-vulcanized and punched to obtain a refrigerant-resistant HNBR sealing ring.
Citation Information
Patent Citations
Process for the continuous dyeing of threads and slivers of dry spun acrylonitrile polymers
CA1025156A
Seal material for refrigerant air conditioning system and preparation method of seal material
CN110724322A
Rubber formula for preventing plastic part from cracking
CN111410780A
Low-temperature-resistant and refrigerant-resistant hydrogenated nitrile rubber and preparation method thereof
CN114044953A
Foaming-resistant HNBR rubber material for shaft seal and preparation method of foaming-resistant HNBR rubber material
CN114230886A
Cited By
Anti-edge-scattering high-strength nylon braid for intelligent wearing and preparation method of anti-edge-scattering high-strength nylon braid
CN120985910A
Low compression set refrigerant resistant hydrogenated nitrile rubber material and method of making
CN122750017A